Routledge Handbook of International Cybersecurity - Eneken Tikk and Mika Kerttunen (New York Routledge, 2020)
School of Arts, Humanities and Social Science
MIR No: 170
Order Date: 2024-08-29
Order No: CU/OPEX/LIBRARY/30/2024-25
Received Date: 2024-09-25
Keywords: Political Science, International Relations, Cyber Security